Pemahaman Menjauhi Zina menurut Pandangan Mufasir - Nafisah binti Ramli (TAFSE: Journal of Qur'anic Studies, 2016)
Social phenomena that occur in today's society, especially young people cannot distinguish between actions that can bring them closer to adultery. To avoid mistakes in understanding religion, it is necessary to study the understanding of the verses of the Qur'an from the opinions of the commentators, both classical and contemporary interpreters. This study is bibliographic in nature, and the data were obtained through the tahlili interpretation method. The main focus of this paper is to see the understanding of the commentators about the verse lâ taqrabu fornication. The results showed that the mufassir understood the meaning of lâ taqrabu adultery to include a prohibition on all actions that encourage adultery, both externally such as dating, ikhtilat between men and women, handshakes between men and women, showing jewelry, wearing perfumes in public places. public, technological advances, as well as internal ones, such as daydreaming, so as to arouse feelings and hearts. Fenomena sosial yang terjadi dalam masyarakat sekarang, terutama kaum muda mudi tidak dapat membedakan perbuatan yang dapat mendekatkan mereka pada zina. Untuk menghindari kekeliruan dalam memahami agama, perlu kajian tentang pemhaman ayat-ayat Al-Qur’an dari pendapat para mufasir, baik penafsir klasik maupun kontemporer. Kajian ini bersifat kepustakaan, dan data didapatkan melalui metode tafsir tahlili. Fokus utama tulisan ini adalah melihat pemahaman para mufasir tentang ayat lâ taqrabu zina. Hasil penelitian menunjukan bahwa mufassir memahami makna lâ taqrabu zina adalah mencakup larangan terhadap seluruh perbuatan yang mendorong kepada perbuatan zina, baik yang bersifat eksternal seperti berpacaran, ikhtilat antara laki dan perempuan, jabat tangan antara laki dan perempuan, memperlihatkan perhiasan, memakai wangi-wangian di depan umum, kemajuan teknologi, maupun yang sifatnya internal, seperti menghayal, sehingga menggugah perasaan dan hati.